Radiological assessment of the angular values of back-lumbar and sacral-lumbar curvature in adolescents - Gonçalves, Giovanna Barros; Pereira, João Santos (Acta Fisiátrica, 2008)
The lumbar region is of great importance in the harmony and maintenance of the erect posture and must be included in any physiotherapeutic evaluation. Due to the difficulty in measuring what is called a "normal" lumbar curvature, this study was carried out with the objective of evaluating lumbar lordosis through the angular measurement of the back-lumbar (L1-L5) and sacral-lumbar (L1-S1) curvatures, to establish the indicative values of those curvatures in adolescents. Methods: 22 asymptomatic young adults of both sexes, aged 14 to 18 years, participated in this study. All volunteers were submitted to radiological assessment in the lumbar region on the sagittal plane, performed at Hospital Doutor Joao Felício in the city of Juiz de Fora, state of Minas Gerais, Brazil. The angular measures of the lumbar curvatures were performed using the Cobb Method, directly over the radiographies. Results: No statistically significant differences were observed regarding gender for the angular values of the back-lumbar (L1-L5) and the sacrallumbar (L1-S1) curvatures. Although there is no consensus in the literature regarding the analysis and definition of the curvature angles of the lumbar column on the sagittal plane, the results have shown to be compatible with the ones reported in literature, with values that are similar to the ones found by other authors. Conclusion: The normative angular values for the back-lumbar and sacral-lumbar curvatures can be established as angular averages of 44.44º and 57.5º, respectively, for asymptomatic adolescents.